How to write instance of state Monad - haskell

I am very new to monads within haskell and i am trying to develop my knowledge with monads ny creating some instances but I am really quite confused with this one i am getting a few errors and have been at it for a bit as i am still unsure any help and explanations are appreciated this is what i have so far, any ideas where i am going wrong?
newtype ST b = S (Int -> (b, Int))
runState :: ST b -> Int -> (b, Int)
runState (S b) st = b st
instance Monad ST where
return :: b -> ST b
return x = S (\st -> (x, st)) the new state with a b
(>>=) :: ST b -> (b -> ST c) -> ST c
c >>= c' = S (\st1 ->
let (b, st2) = runState c st1
(c, st3) = runState (c' b) st2
in (c, st3))

You might have to give implementations for Applicative and Functor as well:
import Control.Applicative
import Control.Monad (liftM, ap)
newtype ST b = S (Int -> (b, Int))
runState :: ST b -> Int -> (b, Int)
runState (S b) st = b st
instance Monad ST where
-- return :: b -> ST b
return x = S (\st -> (x, st)) -- takes in the current state and returns the new state with a b
-- (>>=) :: ST b -> (b -> ST c) -> ST c
c >>= c' = S (\st1 ->
let (b, st2) = runState c st1
(c'', st3) = runState (c' b) st2
in (c'', st3))
instance Applicative ST where
pure = return
(<*>) = ap
instance Functor ST where
fmap = liftM
I found that here.

Related

Haskell Change state in IO function

I'm trying to update a record in an IO-function. I have tried to use the state-monad without success. I saw a comment somewhere that it was possible to solve a similar problem with the state-monad. Is it possible to use the State-monad to do this or do I have to use a monad transformer? If so I would be grateful for a short explanation on how to do it.
{-# LANGUAGE GADTs #-}
data CarState = CS {color :: String }
initState :: CarState
initState = CS {color = "white"}
data Car where
ChangeColor :: String -> Car
func :: Car -> CarState -> IO ()
func (ChangeColor col) cs = do
putStrLn ("car is " ++ show(color cs))
-- Change state here somehow
-- colorChange "green"
putStrLn ("car is now" ++ show(color cs))
main :: IO ()
main = func (ChangeColor "green") initState
colorChange :: String -> MyState CarState String
colorChange col = do
cs <- get
put $ cs {color = col}
return col
data MyState s a = St (s -> (a,s))
runSt :: MyState s a -> s -> (a,s)
runSt (St f) s = f s
evalSt :: MyState s a -> s -> a
evalSt act = fst . runSt act
get :: MyState s s
get = St $ \s -> (s,s)
put :: s -> MyState s ()
put s = St $ \_ -> ((),s)
instance Monad (MyState s) where
return x = St $ \s -> (x,s)
(St m) >>= k = St $ \s_1 -> let (a, s_2) = m s_1
St k_m = k a
in k_m s_2
instance Functor (MyState s) where
fmap f (St g) = St $ \s0 -> let (a, s1) = g s0
in (f a, s1)
instance Applicative (MyState s) where
pure a = St (\s -> (a,s))
(<*>) (St sa) (St sb) = St (\s0 -> let (fn, s1) = sa s0
(a, s2) = sb s1
in (fn a, s2))
In Haskell you cannot mutate data in place, ever, by any mechanism. At all.1
The way state updates are modeled in Haskell is by producing a new value, which is identical to the old value, except for the "updated" bit.
For example, what you're trying to do would be expressed like this:
func :: Car -> CarState -> CarState
func (ChangeColor c) cs = cs { color = c }
1 Well, ok, technically you can sometimes, but it only works for data that has been arranged in advance to be mutable, and it is usually quite cumbersome. Not a normal way to write programs.

How to derive a state monad from first principles?

I am trying to come up with an implementation of State Monad derived from examples of function composition. Here I what I came up with:
First deriving the concept of Monad:
data Maybe' a = Nothing' | Just' a deriving Show
sqrt' :: (Floating a, Ord a) => a -> Maybe' a
sqrt' x = if x < 0 then Nothing' else Just' (sqrt x)
inv' :: (Floating a, Ord a) => a -> Maybe' a
inv' x = if x == 0 then Nothing' else Just' (1/x)
log' :: (Floating a, Ord a) => a -> Maybe' a
log' x = if x == 0 then Nothing' else Just' (log x)
We can have function that composes these functions as follows:
sqrtInvLog' :: (Floating a, Ord a) => a -> Maybe' a
sqrtInvLog' x = case (sqrt' x) of
Nothing' -> Nothing'
(Just' y) -> case (inv' y) of
Nothing' -> Nothing'
(Just' z) -> log' z
This could be simplified by factoring out the case statement and function application:
fMaybe' :: (Maybe' a) -> (a -> Maybe' b) -> Maybe' b
fMaybe' Nothing' _ = Nothing'
fMaybe' (Just' x) f = f x
-- Applying fMaybe' =>
sqrtInvLog'' :: (Floating a, Ord a) => a -> Maybe' a
sqrtInvLog'' x = (sqrt' x) `fMaybe'` (inv') `fMaybe'` (log')`
Now we can generalize the concept to any type, instead of just Maybe' by defining a Monad =>
class Monad' m where
bind' :: m a -> (a -> m b) -> m b
return' :: a -> m a
instance Monad' Maybe' where
bind' Nothing' _ = Nothing'
bind' (Just' x) f = f x
return' x = Just' x
Using Monad' implementation, sqrtInvLog'' can be written as:
sqrtInvLog''' :: (Floating a, Ord a) => a -> Maybe' a
sqrtInvLog''' x = (sqrt' x) \bind'` (inv') `bind'` (log')`
Trying to apply the concept to maintain state, I defined something as shown below:
data St a s = St (a,s) deriving Show
sqrtLogInvSt' :: (Floating a, Ord a) => St a a -> St (Maybe' a) a
sqrtLogInvSt' (St (x,s)) = case (sqrt' x) of
Nothing' -> St (Nothing', s)
(Just' y) -> case (log' y) of
Nothing' -> St (Nothing', s+y)
(Just' z) -> St (inv' z, s+y+z)
It is not possible to define a monad using the above definition as bind needs to be defined as taking in a single type "m a".
Second attempt based on Haskell's definition of State Monad:
newtype State s a = State { runState :: s -> (a, s) }
First attempt to define function that is built using composed functions and maintains state:
fex1 :: Int->State Int Int
fex1 x = State { runState = \s->(r,(s+r)) } where r = x `mod` 2`
fex2 :: Int->State Int Int
fex2 x = State { runState = \s-> (r,s+r)} where r = x * 5
A composed function:
fex3 x = (runState (fex2 y)) st where (st, y) = (runState (fex1 x)) 0
But the definition newtype State s a = State { runState :: s -> (a, s) } does not fit the pattern of m a -> (a -> m b) -> m b of bind
An attempt could be made as follows:
instance Monad' (State s) where
bind' st f = undefined
return' x = State { runState = \s -> (x,s) }
bind' is undefined above becuase I did not know how I would implement it.
I could derive why monads are useful and apply it the first example (Maybe') but cannot seem to apply it to State. It will be useful to understand how I could derive the State Moand using concepts defined above.
Note that I have asked a similar question earlier: Haskell - Unable to define a State monad like function using a Monad like definition but I have expanded here and added more details.
Your composed function fex3 has the wrong type:
fex3 :: Int -> (Int, Int)
Unlike with your sqrtInvLog' example for Maybe', State does not appear in the type of fex3.
We could define it as
fex3 :: Int -> State Int Int
fex3 x = State { runState = \s ->
let (y, st) = runState (fex1 x) s in
runState (fex2 y) st }
The main difference to your definition is that instead of hardcoding 0 as the initial state, we pass on our own state s.
What if (like in your Maybe example) we wanted to compose three functions? Here I'll just reuse fex2 instead of introducing another intermediate function:
fex4 :: Int -> State Int Int
fex4 x = State { runState = \s ->
let (y, st) = runState (fex1 x) s in
let (z, st') = runState (fex2 y) st in
runState (fex2 z) st' }
SPOILERS:
The generalized version bindState can be extracted as follows:
bindState m f = State { runState = \s ->
let (x, st) = runState m s in
runState (f x) st }
fex3' x = fex1 x `bindState` fex2
fex4' x = fex1 x `bindState` fex2 `bindState` fex2
We can also start with Monad' and types.
The m in the definition of Monad' is applied to one type argument (m a, m b). We can't set m = State because State requires two arguments. On the other hand, partial application is perfectly valid for types: State s a really means (State s) a, so we can set m = State s:
instance Monad' (State s) where
-- return' :: a -> m a (where m = State s)
-- return' :: a -> State s a
return' x = State { runState = \s -> (x,s) }
-- bind' :: m a -> (a -> m b) -> m b (where m = State s)
-- bind' :: State s a -> (a -> State s b) -> State s b
bind' st f =
-- Good so far: we have two arguments
-- st :: State s a
-- f :: a -> State s b
-- We also need a result
-- ... :: State s b
-- It must be a State, so we can start with:
State { runState = \s ->
-- Now we also have
-- s :: s
-- That means we can run st:
let (x, s') = runState st s in
-- runState :: State s a -> s -> (a, s)
-- st :: State s a
-- s :: s
-- x :: a
-- s' :: s
-- Now we have a value of type 'a' that we can pass to f:
-- f x :: State s b
-- We are already in a State { ... } context, so we need
-- to return a (value, state) tuple. We can get that from
-- 'State s b' by using runState again:
runState (f x) s'
}
Have a look to this. Summing and extending a bit.
If you have a function
ta -> tb
and want to add "state" to it, then you should pass that state along, and have
(ta, ts) -> (tb, ts)
You can transform this by currying it:
ta -> ts -> (tb, ts)
If you compare this with the original ta -> tb, we obtain (adding parentheses)
ta -> (ts -> (tb, ts))
Summing up, if a function returns tb from ta (i.e. ta -> tb), a "stateful"
version of it will return (ts -> (tb, ts)) from ta (i.e. ta -> (ts -> (tb, ts)))
Therefore, a "stateful computation" (just one function, or either a chain of functions dealing with state) must return/produce this:
(ts -> (tb, ts))
This is the typical case of a stack of ints.
[Int] is the State
pop :: [Int] -> (Int, [Int]) -- remove top
pop (v:s) -> (v, s)
push :: Int -> [Int] -> (int, [Int]) -- add to the top
push v s -> (v, v:s)
For push, the type of push 5 is the same than type of pop :: [Int] -> (Int, [Int]).
So we would like to combine/join this basic operations to get things as
duplicateTop =
v <- pop
push v
push v
Note that, as desired, duplicateTop :: [Int] -> (Int, [Int])
Now: how to combine two stateful computations to get a new one?
Let's do it (Caution: this definition is not the same that the
used for the bind of monad (>>=) but it is equivalent).
Combine:
f :: ta -> (ts -> (tb, ts))
with
g :: tb -> (ts -> (tc, ts))
to get
h :: ta -> (ts -> (tc, ts))
This is the construction of h (in pseudo-haskell)
h = \a -> ( \s -> (c, s') )
where we have to calculate (c, s') (the rest in the expressions are just parameters a and s). Here it is how:
-- 1. run f using a and s
l1 = f a -- use the parameter a to get the function (ts -> (tb, ts)) returned by f
(b, s1) = l1 s -- use the parameter s to get the pair that l1 returns ( :: (tb, ts) )
-- 2. run g using f output, b and s1
l2 = g b -- use b to get the function (ts -> (tb, ts)) returned by g
(c, s') = l2 s1 -- use s1 to get the pair that l2 returns ( :: (tc, ts) )

Safely generalize ST return value

I have an ST extractor foo :: (forall s . ST s a) -> b for some concrete a and b. Could I safely make another function fooC :: (forall s . ST s (a, c)) -> (b, c), which would allow me to return some additional value out of the ST computation? Can there be a generic transformation addC :: ((forall s . ST s a) -> b) -> (forall s1 . ST s1 (a,c)) -> (b,c) which would be safe to use?
I'm not really sure I understand what you're trying to accomplish, but this has the right type:
addC :: ((forall s . ST s a) -> b)
-> (forall s1 . ST s1 (a,c)) -> (b,c)
addC f m = runST $ (\(a,c) -> (f (pure a), c)) <$> m
Note that (forall s. ST s a) is isomorphic to a (as witnessed by pure and runST), so maybe you should just take a function a -> b and a value (a, c).

how to implement mapAccumM?

I want mapM over something that is traversable while passing an accumulator. I came up with:
import Control.Applicative
import Data.Traversable
import Control.Monad.State
mapAccumM :: (Applicative m, Traversable t, MonadState s m)
=> (s -> a -> m (s, b)) -> s -> t a -> m (t b)
mapAccumM f acc0 xs = put acc0 >> traverse g xs
where
g x = do
oldAcc <- get
(newAcc, y) <- f oldAcc x
put newAcc
return y
How can this be done without State monad?
roconnor answered this for me on #haskell
this solves my problem but notice that accumulator is returned in the second element of the tuple instead of the first
mapAccumM :: (Monad m, Functor m, Traversable t) => (a -> b -> m (c, a)) -> a -> t b -> m (t c)
mapAccumM f = flip (evalStateT . (Data.Traversable.traverse (StateT . (flip f))))
or to also return the accumulator:
mapAccumM' :: (Monad m, Functor m, Traversable t) => (a -> b -> m (c, a)) -> a -> t b -> m (t c, a)
mapAccumM' f = flip (runStateT . (Data.Traversable.traverse (StateT . (flip f))))

Functor / Applicative instances for State in Haskell

After reading (and skimming some sections of) Wadler's paper on monads, I decided to work through the paper more closely, defining functor and applicative instances for each of the monads he describes. Using the type synonym
type M a = State -> (a, State)
type State = Int
Wadler uses to define the state monad, I have the following (using related names so I can define them with a newtype declaration later on).
fmap' :: (a -> b) -> M a -> M b
fmap' f m = \st -> let (a, s) = m st in (f a, s)
pure' :: a -> M a
pure' a = \st -> (a, st)
(<#>) :: M (a -> b) -> M a -> M b
sf <#> sv = \st -> let (f, st1) = sf st
(a, st2) = sv st1
in (f a, st2)
return' :: a -> M a
return' a = pure' a
bind :: M a -> (a -> M b) -> M b
m `bind` f = \st -> let (a, st1) = m st
(b, st2) = f a st1
in (b, st2)
When I switch to using a type constructor in a newtype declaration, e.g.,
newtype S a = S (State -> (a, State))
everything falls apart. Everything is just a slight modification, for instance,
instance Functor S where
fmap f (S m) = S (\st -> let (a, s) = m st in (f a, s))
instance Applicative S where
pure a = S (\st -> (a, st))
however nothing runs in GHC due to the fact that the lambda expression is hidden inside that type constructor. Now the only solution I see is to define a function:
isntThisAnnoying s (S m) = m s
in order to bind s to 'st' and actually return a value, e.g.,
fmap f m = S (\st -> let (a, s) = isntThisAnnoying st m in (f a, s))
Is there another way to do this that doesn't use these auxiliary functions?
If you look here, you will see that they define it this way:
newtype State s a = State { runState :: (s -> (a,s)) }
so as to give the inner lambda a name.
The usual way is to define newtype newtype S a = S {runState : State -> (a, State)}. Then instead of your isntThisAnnoying s (S m) you can write runState t s where t is the same as S m.
You have to use a newtype because type synonyms cannot be typeclass instances.

Resources